MANAGEMENT FUNCTIONS TOWARDS ISLAMIC EDUCATION AT MTS MAMBAUL ULUM TULUPARI - Qomariyah, Qomariyah; Hani’, Ummi; Agus R, Abu Hasan (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study aims to explore and analyze the implementation of management functions in Islamic education at MTs Mambaul Ulum Tulupari. The method used in this study is qualitative with a case study approach, which focuses on observation, in-depth interviews, and document analysis related to managerial activities at the school. The management functions that are the focus of this study include planning, organizing, implementing, and supervising in the context of Islamic education. The study results indicate that effective management plays a vital role in achieving the goals of quality Islamic education at MTs Mambaul Ulum Tulupari. A thorough planning process, efficient organization of human resources, implementation of structured education programs, and a continuous supervision system have positively impacted the quality of education. In addition, good communication between school leaders, teachers, and students is also a supporting factor for the success of educational management. This study concludes that implementing optimal management functions at MTs Mambaul Ulum Tulupari can improve the effectiveness of Islamic education and contribute to the formation of students' noble character.